Using the Kazakh national games as a means of educating young people in the learning process (Journal of Educational Sciences, 2017)
The article raises the question about the upbringing side of the Kazakh national games, which along with the classical types of activities organised in the framework curriculum of comprehensive schools, has a beneficial effect on inter-ethnic relations of the peoples of Kazakhstan. Along with the development of physical qualities, the Kazakh national games develop children’s spiritual, moral and volitional qualities, culture. Teaching curricula and programs must take into account the share of the national games as a percentage along with the classic sports like football, athletics, volleyball, basketball, gymnastics and martial arts elements. They are known, to develop motor skills, but mostly sporting events take place in the classic sports, the organizers find it difficult to be pioneers because to carry out classical events is much easier than unfamiliar to debut in the national game. Kazakh national games are famous for fair play, generosity, courage, respect opponents.
Keywords: national games; sporting events; educational programs and plans; education; spirituality; moral qualities